2016
DOI: 10.1186/s12917-016-0918-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Strongylus vulgaris in equine faecal samples by real-time PCR and larval culture – method comparison and occurrence assessment

Abstract: Background Strongylus vulgaris has become a rare parasite in Germany during the past 50 years due to the practice of frequent prophylactic anthelmintic therapy. To date, the emerging development of resistance in Cyathostominae and Parascaris spp. to numerous equine anthelmintics has changed deworming management and the frequency of anthelmintic usage. In this regard, reliable detection of parasitic infections, especially of the highly pathogenic S. vulgaris is essential. In the current study, two diagnostic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
2
14
3
Order By: Relevance
“…In contrast to previous studies reporting a less than 2% S. vulgaris prevalence in Germany using larval culture or DNA-based copromicroscopic methods [ 10 , 16 ], the high S. vulgaris seroprevalence of 32.3% was unexpected and is also astonishing in view of the herein calculated overall fecal S. vulgaris DNA prevalence of 1.1%. However, this is actually less than the 62.2% reported in the only other European field investigation of S. vulgaris sero-prevalence published recently by Scandinavian colleagues [ 36 ], who, in a very similar approach, compared gastro-intestinal parasite infection with intestinal disease status in a total of 259 horses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies reporting a less than 2% S. vulgaris prevalence in Germany using larval culture or DNA-based copromicroscopic methods [ 10 , 16 ], the high S. vulgaris seroprevalence of 32.3% was unexpected and is also astonishing in view of the herein calculated overall fecal S. vulgaris DNA prevalence of 1.1%. However, this is actually less than the 62.2% reported in the only other European field investigation of S. vulgaris sero-prevalence published recently by Scandinavian colleagues [ 36 ], who, in a very similar approach, compared gastro-intestinal parasite infection with intestinal disease status in a total of 259 horses.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the most recent available copromicroscopic German and international study findings, the cyathostomins to date occur almost ubiquitously amongst the strongyles and certainly at much higher rates than large strongyles such as S. vulgaris . The latter apparently occur only in very few horses and farms [ 10 , 11 , 12 ]. This is, however, not necessarily always the case, as recent Scandinavian studies have documented S. vulgaris farm prevalence of sometimes even over 60% [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different surveys showed that the S. vulgaris species is more commonly found in working horses, as it was in the present study, or in horses from farms where anthelmintic treatments are iregularly administered or with a lower intensity (Kyvsgaard et al, 2011). Therefore, due to the intensive anthelmintic treatment regime in the last decades, S. vulgaris is reported now in lower prevalence in well managed farms (Kaplan, 2002) as it is in Switzerland, Germany (Kaspar et al, 2017). In Poland, in slaughtered horses was of S. vulgaris was the most dominant nematode (22.8%), followed by S. edentatus (18.3%) and S. equinus (1.7% ) (Studzińska et al, 2012).…”
Section: Resultsmentioning
confidence: 75%
“…Similarly, in Denmark a higher prevalence of S. vulgaris was observed on farms using selective treatment compared to farms deworming on a regular basis ( Nielsen et al, 2012 ). In contrast, low prevalences of S. vulgaris (0.2–1.3%) have been reported from Germany ( Schneider et al, 2014 , Kaspar et al, 2017 ). However, selective treatment is not implemented as strict in Germany compared to Sweden and Denmark and many horses are still routinely dewormed ( Schneider et al, 2014 ).…”
Section: Discussionmentioning
confidence: 89%
“…More importantly though, in this study were all samples analysed individually compared to pooled samples from four horses in 1999 ( Lind Osterman et al, 1999 ). In addition, was S. vulgaris diagnosed with a specific PCR, which is considered to be a more sensitive method than the traditional morphological identification of harvested larvae from cultures ( Kaspar et al, 2017 ). However, a relatively recent study from Denmark also found a high prevalence of S. vulgaris although the results were based on morphological identification of larvae ( Nielsen et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%